Passage of intestinal (small bowel) cast – an unusual complication of neutropenic sepsis. (26th July 2010) - Samee, A; Kirby, R M; Brunt, A M
Abstract : A 52-year-old woman was admitted with neutropenic sepsis, 3 days following the final cycle of adjuvant chemotherapy for breast cancer. Her condition deteriorated with progressive abdominal distension, bilious vomiting and diarrhoea. Abdominal examination revealed a mild degree of peritonism. Five days later she passed a small bowel cast per rectum, showing gross fungal contamination on histology. She was managed conservatively with antibiotics and antifungal medications and nutritional support.